A Note To Myself, We’re Alright: A Poetry Collection as Therapy in the Pandemic Times - Ordoñez, Cris Heila M. (Animo Repository, 2022)
A Note To Myself, We’re Alright is a poetry collection inspired by the author’s mood and state of mind. The artwork is composed of different types of poetry that best fits the author’s aesthetic. The poetry collection is intended to help those who are troubled in mind be at ease. The artwork aims to be an aid to people, especially to the youth in this era. The unfamiliar lifestyle that came from the COVID-19 pandemic caused some mental difficulties to us all. The research paper is based on a phenomenological theory which aims to question personal experiences to one self and their world at the center of analyses of personality change. Though the paper relies on related literature, I conducted a semi-formal interview with students who have the same troubles as I do. As for the writing process of my poetry collection, I created my own personal journal every day for a week. In this week, I would write down how my day went, the difficulties I experienced, and how I felt as I underwent the pandemic. The next step is to create the actual poems with reference to the journal entries I wrote in my personal journal. A total of 7 poems will be created regarding the problems I encountered from the week I wrote down my personal diary. I also will be creating more poems to be the realization or the answer to the troubles I felt from my personal diary.